EXPERIENCE OF USING THE NONSELECTIVE ENDOTHELIN RECEPTOR ANTAGONIST MACITENTAN IN PATIENTS WITH PULMONARY ARTERIAL HYPERTENSION - M. A. Simakova; N. S. Goncharova; E. V. Karelkina; O. M. Moiseeva (Кардиоваскулярная терапия и профилактика, 2018)
Aim. To present the results of treatment with macitentan of patients included in the clinical trial SERAPHIN in Almazov National Medical Research Centre and define target therapy of pulmonary arterial hypertension (PAH) in real clinical practice.Material and methods. The article presents the results of the 151 patients with PAH followedup in Almazov National Medical Research Centre from 2009 to 2016.Results. Fiveyear survival of PAH patients included in the register of Almazov National Medical Research Centre reached 77% for idiopathic PAH, 52% for PAH associated with systemic scleroderma, 81% for PAH associated with nonrepaired congenital heart disease, 82% for patients with repaired congenital shunts and 100% for PAH associated with human immunodeficiency virus infection. The group that received PAH specific monotherapy consisted of 47% (n=71) of patients among which phosphodiesterase type 5 inhibitor (PDE5i) sildenafil was undoubtedly the most prescribed drug — 74% (n=53). The group that received combined PAH specific therapy consisted of 66 (44%) patients: 48 patients received various twocomponent therapy, 18 patients — threecomponent therapy with endothelin receptor antagonist in combination with PDE5i and prostanoids. 11 patients with PAH were included in SERAPHIN study of which 9 patients had been already receiving generic PDE5i therapy. In macitentan group, a statistically significant increase in the 6minute walk distance (+50 meters) and a decrease in hemodynamic parameters such as mean right atrial pressure (2,3 mm Hg) and pulmonary vascular resistance (445 dynsec/cm5) were observed after 6 months. No patient had a clinically significant increase in liver transaminases or a decrease in hemoglobin levels.Conclusion. Improvement of prognosis in PAH patients according to the register of the Centre is connected both with early detection of the disease, thanks to the development of specialized healthcare, and more frequent use of combination therapy. Macitentan proved its longterm efficacy and safety as monotherapy and in combination with PDE5i.